Interaksi Guru Pamong dan Mahasiswa Pratek Lapangan Pasca Pandemi Covid-19 - Jesy Agustin; Reno Fernandes (Universitas Negeri Padang, 2022)
This study aims to analyze the Implementation of Field Practices after the Covid-19 Pandemic Study of Interaction between Civil Service Teachers and Students at SMAN 1 Nan Sabaris Padang Pariaman in the implementation of PLK, that isi where the student learning process takes place to become a teacher. Therefore, civil servant teacher and students must establish a good relationship. However, in the implementation of PLK, civil servant teachers do not carry out their roles as stated in the PLK manual. So from this problem there is a discrepancy in the implementation of PLK. So that the problem leads to a pattern of dissociative social interaction between tutors and student. This research was analyzed using Gerge Simmel theory of Subordinate and Superordinate. The approach used is a case study qualitative approach. This research uses a purposive sampling technique 18 informants consisting of 10 teachers and 8 students. The data collection techniques used in this study were observation, interviews and document studi. For this research data, the authours used triangulation data, the data werw analyzed using the Mathew B Milles and A Michael Huberman models, incliding the stages of data reduction, data presentation, and conclusion. Hand research this shows that the reason for the establishment of social dissociative interactions between the civil teachers and student is that the civil sevant teachers has the authority to deal with students, students are less socialized at shool, tutors are constrained in the use of technology, tutors do not guide students based on their roles, and assignments by civil servant teachers are outside the student responsibility.